Organização do espaço agrário e dinâmica em área de expansão periurbana no município de Rio Claro-SP - Murbach, Beatriz Aggio [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Changes in rural areas began in the second half of the 20th century, influenced by the modernization of agriculture. In this way changes are inserted not only in the forms of production, but also in the paradigms of consumption and consequently in the economic and social aspects that involve the rural world. As a result of this modernization, it can be pointed the aggravation of social differences, since this movement was unequal and excluding. The presented context composes the main aspects for rural resignification or New Rural.The discussion moves towards understanding the dimension of the urban and the rural, using the concept of a continuum, according to which in some areas the urban transposes the urban limits, in order to constitute levels of gradation. This transition zone is defined as Periurban, where there is a mixture of rural and urban activities and the land dispute. The present work seeks to characterize and analyze the temporal evolution of the area that includes the extension of the industrial district and the rural area of the municipality of Rio Claro-SP, the Nicolau Marotti Road. The proposal of the analysis consists of understanding the dynamics in this area of the municipality, with a marked rural history, faced by the industrial area

As mudanças no espaço rural tiveram início na segunda metade do século XX, por influência da modernização da agricultura. Dessa forma inserem-se mudanças não apenas nas formas de produzir, mas também nos paradigmas de consumo e consequentemente nos aspectos econômicos e sociais que envolvem o mundo rural. Como resultados dessa modernização, temos o agravamento das diferenças sociais, visto que esse movimento fora desigual e excludente. O contexto apresentado compõe aspectos principais para ressignificação do rural ou Novo Rural. A discussão caminha no sentido de entender a dimensão do urbano e do rural, utilizando-se do conceito de continuum, no qual algumas áreas, o urbano passa a transpor os limites urbanos, de maneira a constituir níveis de gradação. Essa zona de transição é definida como Periurbana, onde se tem um mesclar de atividades rurais e urbanas e a disputa pelo solo. O presente trabalho busca realizar uma caracterização e análise temporal da área que compreende o prolongamento do distrito industrial e o espaço rural do município de Rio Claro-SP, a Estrada Nicolau Marotti. A proposta de análise consiste em compreender as dinâmicas nessa área do município, com histórico marcadamente rural, faceado pela área industrial
Keywords: Geografia rural; Geografia agrícola; Agricultura; Estradas vicinais; Rio Claro (SP)